2012
DOI: 10.1590/s0103-84782012005000019
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento in vitro e aclimatização de Cattleya loddigesii Lindley (Orchidaceae) com carvão ativado sob dois espectros luminosos

Abstract: IVCrescimento in vitro e aclimatização de Cattleya loddigesii Lindley (Orchidaceae) com carvão ativado sob dois espectros luminosos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
1
8
1
1
Order By: Relevance
“…The chlorophyll a/b ratio was negatively correlated with the ratio of red to blue light. Galdiano et al (2012) showed that red light strongly promoted chlorophyll b synthesis in Cattleya loddigesii Lindl.. Similar results were also reported for R. glutinosa and Triticum aestivum L. (Dong et al, 2014; Manivannan et al, 2015).…”
Section: Discussionsupporting
confidence: 82%
“…The chlorophyll a/b ratio was negatively correlated with the ratio of red to blue light. Galdiano et al (2012) showed that red light strongly promoted chlorophyll b synthesis in Cattleya loddigesii Lindl.. Similar results were also reported for R. glutinosa and Triticum aestivum L. (Dong et al, 2014; Manivannan et al, 2015).…”
Section: Discussionsupporting
confidence: 82%
“…The results for the percentage survival observed in this study differ from those obtained by GALDIANO JUNIOR et al (2012). The authors verified that plants of Cattleya loddigesii Lindl.…”
Section: Resultscontrasting
confidence: 72%
“…This fact has already been noted in studies with Azorina vidalli ; Disanthus cercidifolius and cultivars of Rhododendron (MARKS & SIMPSON, 1999); Prunus sp. (MULEO, 2001) and in Cattleya lodigessi (ARAÚJO et al, 2009). However D. phalaenopsis Deang Suree did not respond significantly with respect to the length of pseudo bulbs, relative to the treatments.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations